The Dark Side of the Force – Constraints and Complications of Cell Therapies for Stroke - Boltze, Johannes; Arnold, Antje; Walczak, Piotr; Jolkkonen, Jukka; Cui, Lili; Wagner, Daniel-Christoph (Frontiers in Neurology, 2015)
Cell therapies are increasingly recognized as a promising option to augment the limited therapeutic arsenal available to fight ischemic stroke. During the last two decades, cumulating preclinical evidence has indicated a substantial efficacy for most cell treatment paradigms and first clinical trials are currently underway to assess safety and feasibility in patients. However, the strong and still unmet demand for novel stroke treatment options and exciting findings reported from experimental studies may have drawn our attention away from potential side effects related to cell therapies and the ways by which they are commonly applied. This review summarizes common and less frequent adverse events that have been discovered in preclinical and clinical investigations assessing cell therapies for stroke. Such adverse events range from immunological and neoplastic complication over seizures to cell clotting and cell-induced embolism. It also describes potential complication of clinically applicable administration procedures, detrimental interactions between therapeutic cells and the pathophysiological environment they are placed into, as well as problems related to cell manufacturing. Virtually each therapeutic intervention comes at a certain risk for complications. Side effects do therefore not generally compromise the value of cell treatments for stroke, but underestimating such complications might severely limit therapeutic safety and efficacy of cell treatment protocols currently under development. On the other hand, a better understanding will provide opportunities to further improve existing therapeutic strategies and might help to define those circumstances, under which an optimal effect can be realized. Hence, the review eventually discusses strategies and recommendations allowing us to prevent or at least balance potential complications in order to ensure the maximum therapeutic benefit at minimum risk for stroke patients.